IMPROVING SCIENCE PROCESS SKILLS OF ELEMENTARY SCHOOL STUDENTS BY USING PROBLEM BASED LEARNING APPROACH - Lifda Sari. S; Yanti Fitria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the fact that many elementary school students still had low process skills. The purpose of this research was to improve the process skills of elementary school students by using PBL. This research was a classroom action research using Mac Taggart design. This design consisted of planning, implementation, observation, and reflection. This research was conducted at SDN 39 Mata Air Padang involving 30 students. This research was carried out in 2 cycles. The data were collected through observation sheets in the form of checklist which had been adjusted to measure the process skills. The indicators of process skills included skills for asking questions, making observations, identifying and classifying the results of observations being done, ability to interpret, skills in using tools and materials, planning activities, skills in using concepts obtained under new conditions, and the ability to present research results. Then, the data were analyzed by using two techniques, namely classical learning analysis technique and individual analysis technique. The results revealed that there was an improvement in the process skills of elementary school students after the implementation of PBL model. It was found that the average score in cycle 1 was 66.67 and it increased to 83.33 in cycle 2. The implications of this research served as the basis for teachers in developing the process skills of elementary school students.